Women and Power in Early Islamic History: Jawari of the Abbasid Court (786-861 AD) - Hannan, Haukil; Syaie, Akhmad Najibul Khairi (Universitas Islam Negeri Sumatera Utara, 2024)
The significant presence of jawari owned by the caliphs of Islam became a phenomenon during the early period (170 AH/ 786 AD-247 AH/861 AD) of Abbasid rule. This article aims to examine why the early Abbasid rulers (786-861 AD)